1992
DOI: 10.1080/0141192920180407
|View full text |Cite
|
Sign up to set email alerts
|

Group Child Interviews as a Research Tool

Abstract: Group interviews have several advantages over individual interviews. In particular they help to reveal consensus views, may generate richer responses by allowing participants to challenge one another's views, may be used to verify research ideas or data gained through other methods and may enhance the reliability of children's responses. There are, however, difficulties in carrying out group interviews and they require skilful and sensitive guidance by the interviewer. There have been few reports of their use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
132
1
7

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(141 citation statements)
references
References 9 publications
1
132
1
7
Order By: Relevance
“…This is by no means specific to research with children as respondents of any age may find it difficult to provide spontaneous examples to illustrate particular issues which emerge during the course of an interview. It also partly explains why some children in this study found the group interview easier as something one of the others said might spark off a memory of particular incidences (Lewis, 1992). It was not only difficult for some children to think of examples of their sibship interactions but some also found it hard to express the ambivalence of their love/hate relationships:…”
Section: Task-based Interview Toolsmentioning
confidence: 96%
See 1 more Smart Citation
“…This is by no means specific to research with children as respondents of any age may find it difficult to provide spontaneous examples to illustrate particular issues which emerge during the course of an interview. It also partly explains why some children in this study found the group interview easier as something one of the others said might spark off a memory of particular incidences (Lewis, 1992). It was not only difficult for some children to think of examples of their sibship interactions but some also found it hard to express the ambivalence of their love/hate relationships:…”
Section: Task-based Interview Toolsmentioning
confidence: 96%
“…There was slightly less pressure in the group situation, "Didn't have to think all yourself" (GM), as ideas could be shared and sparked off each other (see also Lewis, 1992;Punch 2002b):…”
Section: Comparing Group and Individual Interviewsmentioning
confidence: 99%
“…First, focus groups provide descriptions about perceptions of the program participants and they are not useful for testing hypotheses in the traditional experimental design. Second, although the group interaction is generally seen as an advantage of focus groups, Lewis [44] argued that there is always the possibility that intimidation within the group setting may inhibit interaction. Another obstacle is not encountered in individual interviews is scheduling a time and location convenient to all participants.…”
Section: Discussionmentioning
confidence: 99%
“…So the data necessary for the research as well as the outcomes emerge from the interaction of the group participants. The reason of choosing this alternative of the personal inquiry was the fact, that a group interview can generate a wider range of responses than it is generated in individual interviews (Lewis, 1992) and can be useful for gaining an insight into what might be pursued in subsequent individual interviews (Bogdan, & Biklen, 1992).…”
Section: Methodsmentioning
confidence: 99%